2019
DOI: 10.1002/term.2838
|View full text |Cite
|
Sign up to set email alerts
|

Substrate elasticity induces quiescence and promotes neurogenesis of primary neural stem cells—A biophysical in vitro model of the physiological cerebral milieu

Abstract: In the brain, neural stem cells (NSC) are tightly regulated by external signals and biophysical cues mediated by the local microenvironment or “niche.” In particular, the influence of tissue elasticity, known to fundamentally affect the function of various cell types in the body, on NSC remains poorly understood. We, accordingly, aimed to characterize the effects of elastic substrates on critical NSC functions. Primary rat NSC were grown as monolayers on polydimethylsiloxane‐ (PDMS‐) based gels. PDMS‐coated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…We previously proposed polydimethylsiloxane (PDMS)based substrates as a suitable in vitro model for the investigation of mechanical influences, given smooth surface topography and excellent biocompatibility (Schellenberg et al, 2014;Abraham et al, 2019;Blaschke et al, 2019). We here hypothesize that the ubiquitous influence of substrate elasticity modulates primary microglia functions and might even alter dynamic microglia reaction upon subsequent stimuli.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We previously proposed polydimethylsiloxane (PDMS)based substrates as a suitable in vitro model for the investigation of mechanical influences, given smooth surface topography and excellent biocompatibility (Schellenberg et al, 2014;Abraham et al, 2019;Blaschke et al, 2019). We here hypothesize that the ubiquitous influence of substrate elasticity modulates primary microglia functions and might even alter dynamic microglia reaction upon subsequent stimuli.…”
Section: Introductionmentioning
confidence: 94%
“…We and others have previously shown that a simulation of mechanical properties on CNS cells in vitro is feasible and allows analyzing cell functions under more physiological conditions than provided by regular cell cultures, uncovering essential aspects and mechanobiological properties of neural stem cells and neurons (Pathak et al, 2014;Abraham et al, 2019;Blaschke et al, 2019). Overall, mechanical properties alter the development and behavior not only of mesenchymal stem cells (Murphy et al, 2011), hematopoietic stem cells (Kumar et al, 2013), and cardiomyocytes (Hersch et al, 2013) but also of neural cells like neurons (Abraham et al, 2019), astrocytes (Moshayedi et al, 2014), and neural stem cells (Blaschke et al, 2019). While single reports describe morphological alterations of microglia dependent on underlying substrate elasticity (Moshayedi et al, 2014;Bollmann et al, 2015), the impact of elasticity on microglia at the functional level to date remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness of the matrix mainly affects the differentiation of NSCs into different cell phenotypes. When the stiffness of the matrix is approximately 1 kPa, NSCs are more easily differentiated into neurons ( Rammensee et al, 2017 ; Blaschke et al, 2019 ). Leipzig and Shoichet (2009) developed a photopolymerized methylacrylamide chitosan biomaterial with a Young’s modulus adjustable from less than 1 kPa to greater than 30 kPa.…”
Section: Regulation Of Physical Cues On Neuronal Behaviormentioning
confidence: 99%
“…On 1 kPa PDMS, the number of neurons was 42%, while on 50 kPa PDMS, the number of neurons was 25%. Neurons from NSCs on 1 kPa PDMS showed 29% longer neurites compared with those on stiffer PDMS substrates, suggesting optimized neuronal maturation and an accelerated generation of neuronal networks ( Blaschke et al, 2019 ). If the stiffness of the matrix exceeds or decreases below a certain range (∼1 kPa), the proportion of neurons will decrease.…”
Section: Regulation Of Physical Cues On Neuronal Behaviormentioning
confidence: 99%
See 1 more Smart Citation